Autologous bone marrow cell therapy for peripheral arterial disease - Botti C (Dove Medical Press, 2012)
C Botti, C Maione, A Coppola, V Sica, G CobellisDepartment of General Pathology, Second University of Naples, Naples, ItalyAbstract: Inadequate blood supply to tissues caused by obstruction of arterioles and/or capillaries results in ischemic injuries – these injuries can range from mild (eg, leg ischemia) to severe conditions (eg, myocardial infarction, stroke). Surgical and/or endovascular procedures provide cutting-edge treatment for patients with vascular disorders; however, a high percentage of patients are currently not treatable, owing to high operative risk or unfavorable vascular involvement. Therapeutic angiogenesis has recently emerged as a promising new therapy, promoting the formation of new blood vessels by the introduction of bone marrow–derived stem and progenitor cells. These cells participate in the development of new blood vessels, the enlargement of existing blood vessels, and sprouting new capillaries from existing blood vessels, providing evidence of the therapeutic utility of these cells in ischemic tissues. In this review, the authors describe peripheral arterial disease, an ischemic condition affecting the lower extremities, summarizing different aspects of vascular regeneration and discussing which and how stem cells restore the blood flow. The authors also present an overview of encouraging results from early-phase clinical trials using stem cells to treat peripheral arterial disease. The authors believe that additional research initiatives should be undertaken to better identify the nature of stem cells and that an intensive cooperation between laboratory and clinical investigators is needed to optimize the design of cell therapy trials and to maximize their scientific rigor. Only this will allow the results of these investigations to develop best clinical practices. Additionally, although a number of stem cell therapies exist, many treatments are performed outside international and national regulations and many clinical trials have been not registered on databases such as ClinicalTrials.gov or EudraCT. Therefore, more rigorous clinical trials are required to confirm the first hopeful results and to address the challenging issues.Keywords: adult stem cells, critical limb ischemia, bone marrow transplantation, therapeutic angiogenesis